Modeling the selection of innovative strategy for development of industrial enterprises - Mironova, Nadya; Koptieva (Fadieieva), H. M.; Liganenko, Iryna; Sakun, Ayta; Chernyak, Daryna (My University, 2022)
The assessment of the state of the innovation sphere of Poland in relation to the world level shows that Poland has educational and scientific potential allowing to produce scientific ideas and developments but the level of their commercialization remains low. As a result, Poland lags in terms of such criteria for the development of innovation sphere as labor productivity and financial support for innovation activities. The methodological basis of the study is the theory of fuzzy sets and the matrix approach – in modeling the selection of strategies to stimulate innovative development of industrial enterprises. The construction of a matrix of strategies is based on the diagnosis of the total potential of industrial enterprises and the level of its implementation in the innovation sphere. Modeling of the selection of innovation development strategy for industrial entities based on the use of fuzzy set theory in assessing the level of investment attractiveness and innovation potential of enterprises is carried out. Based on the proposed methodological approach, the strategic directions of innovative development of three Polish industrial enterprises are substantiated.
Keywords: innovative strategy; industrial enterprise; management; development; potential; matrix